Development of a reliable and valid adolescence nutritional knowledge questionnaire - Oz, Fatih; Aydin, Resat; Onsuz, Muhammed Fatih; Metintas, Selma; Emiral, Gulsum Ozturk (Progress in Nutrition, 2016)
We aimed to develop a valid and reliable questionnaire to measure the knowledge level of adolescents. We performed a comprehensive literature review and chose 49 items for the questionnaire. Totally 11 items were excluded from the questionnaire. Spearman’s rank correlation coefficient was used to measure the level of agreement between responses at test and re-test. Finally, the questionnaire consisted of 38 items and three subscales, including 12 items that were incorrect statements. The adolescent population who participated in the study included 43.9% boys, and 56.1% girls. A total of 9.7% were overweight, and 4.6% were obese. Cronbach’s alpha coefficient was 0.85 overall. Retest reliability scores were significant (r = 0.69, P < 0.001). Median scores from the questionnaire were lower in boys (Median: 24 min: 0, max: 34) than girls (Median: 26 min: 7, max: 36) and in adolescents living in rural areas (median: 22, min: 7, max: 32) compared with those living in urban areas (median: 26 min: 0, max: 36) (p<0.001). The instrument is a practical and easy-to-administer tool with acceptable reliability in high school students.